Merchants, companies, and trade: Europe and Asia in the early modern era - Morineau, Michel; Chaudhury, Sushil (Cambridge University Press, 2009)
Written by well-known scholars, this book raises pertinent questions and takes up alternate perspectives on the growth and development of international trade between Europe and Asia, especially India, in the sixteenth to eighteenth centuries. Through a comparative and comprehensive study of merchant communities, markets and commodities the individual authors argue, contrary to conventional views, that Asian merchants were in no way inferior to Europeans in terms of their commercial operations and business acumen. The book emphasizes the continuing and growing importance of India's overland trade, even in the seventeenth to eighteenth centuries, traces the little-known world of Armenian merchants, the hitherto obscure, but voluminous, Indian trade with the Ottoman Empire, and by unearthing new evidence, demonstrates that the export activity of Asian merchants through the overland route from Bengal was higher, in fact, than the combined total of European exports
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: 1500-1800; 00.00.1990; Asia -- Commerce -- History -- Congresses; Asia -- Commerce -- Europe -- History -- Congresses; Europe -- Commerce -- Asia -- History -- Congresses; Europe -- Commerce -- History -- Congresses; Konferenzschrift; Geschichte 1500-1800; Außenhandel; Europa